1972
DOI: 10.21273/jashs.97.4.437
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium on Respiration of Apples1

Abstract: Respiration of apples was inversely related to Ca content of flesh. Respiration increased markedly if Ca concn was below 110 ppm. High N levels also increased respiration. High Ca successfully counteracted the N effect and kept the respiration at a low level. When N was supplied as ammonium, respiration was higher than when a similar quantity of N was supplied as nitrate. Calcium counteracted the increased respiration induced by ammonium-N. Low Ca fruit lost 30-70% of its capacity to synthetize proteins and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Injury to conducting tissue, girdling, or both probably accounted for the low Ca concn in fruits, as well as for the heavy fruit set. Faust and Shear (6) found that low-Ca fruit had higher respiratory rates. High fruit respiratory rates coupled with impaired downward translocation of assimilates and perhaps hormones that trigger or regulate maturation could have caused the earlier fruit maturity that season.…”
Section: Discussionmentioning
confidence: 98%
“…Injury to conducting tissue, girdling, or both probably accounted for the low Ca concn in fruits, as well as for the heavy fruit set. Faust and Shear (6) found that low-Ca fruit had higher respiratory rates. High fruit respiratory rates coupled with impaired downward translocation of assimilates and perhaps hormones that trigger or regulate maturation could have caused the earlier fruit maturity that season.…”
Section: Discussionmentioning
confidence: 98%
“…The beneficial effect of Ca on firmness retention in fruit stored in air, slow CA, and delayed rapid CA can be attributed to a general reduction in the rates of fruit respiration (1,4) and senescence (14).…”
Section: Discussionmentioning
confidence: 99%
“…(6). It has been suggested that Ca is involved in controlling respiration (12) and can reduce ethylene production (17,21). Others have shown that Ca treatment can cause a slight reduction of respiration and ethylene production of apple fruit at 18°C (26).…”
mentioning
confidence: 99%